Recent Patents on Raman Amplifiers - Wenwen, Fan; Xiangjun, Xin; Ming, Lin; Qi, Zhang; Yongjun, Wang (Recent Patents on Engineering, 2012)
With the increasing requirement of communication rate and capacity, Raman amplifiers are becoming the most promising technologies in optical communication systems. There are many patents about Raman amplifiers. In this paper, some important inventions in the patents about Raman amplifiers published since the last 3 years will be presented as typical examples. This paper will introduce various types of inventions about Raman amplifiers individually: multipleorder Raman amplifiers, tunable multimode pump sources Raman amplifiers, automatic gain control Raman amplifiers and lumped Raman amplifiers with a highly-nonlinear medium. These inventions are classified from the principle of Raman amplification effect, the implementation way, deployment mode and optical materials and devices to realize innovation. Above all, Raman amplifiers are developing towards greater capacity, lower noise and nonlinearity, higher gain and longer fiber span lengths.
Keywords: Amplifiers